Recontraction of Morphological and Morphophonemic Processes in Indonesian: Analysis of Types, Phoneme Changes, and Grammatical Implications - Istiana (Konsultan Jurnal Ilmiah Indonesia, 2026)
The linguistic structure of the Indonesian language depends heavily on word-formation dynamics, which are deeply driven by morphological and morphophonemic operations. This study aims to systematically describe the various types of morphological processes in Indonesian, analyze the patterns of sound alterations inside morphophonemic events, and examine how these two grammatical procedures collaborate to generate new words. This study employed a qualitative library research method by synthesizing authoritative morphological reference frameworks and standard linguistic documents. The data were collected through strategic documentation and notes, followed by descriptive-conceptual analysis to reconstruct structural boundaries. The findings reveal that morphological construction operates through a range of distinct configurations, including affixation, reduplication, compounding (kompositum), abbreviation, metanalysis, analogy, zero derivation, and combined operations. Concurrently, the study demonstrates that morphophonemic behaviors systemically encompass three explicit transformations: phoneme change, phoneme addition, and phoneme loss, which are heavily triggered by the initial phonemic environment of the base morpheme. The study concludes that morphological and morphophonemic processes do not run in isolation but constitute an integrated structural ecosystem that ensures grammatical harmony and phonetic ease in Indonesian word formation.